Seasonal changes in the abundance Fusarium proliferatium, microbial endophytes and nutrient levels in the roots of hybrid bamboo Bambusa pervariabilis × Dendrocalamopsis grandis - Li, Lin; Wang, Yaxuan; Yu, Cailin; Li, Shuying; Lin, Tiantian; Han, Shan; Zhu, Tianhui; Li, Shujiang (Frontiers in Plant Science, 2023)
Plant root pathogens invade the soil around plant roots, disturbing the systemic balance, reducing plant defenses, and causing severe disease. At present, there are few studies on the severity of plant diseases caused by pathogen invasion in different seasons and how pathogens affect root microecology. In this study, we used 16S and ITS amplicon sequencing with Illumina NovaSeq 6000 to compare seasonal changes in the composition and structure of microbial communities from healthy roots of bamboo Bambusa pervariabilis × Dendrocalamopsis grandis and roots infected by the soilborne pathogen Fusarium proliferatum. We also compared the levels of nutrients in the root tissues of the two groups of plants. We identified the lesion area and relative abundance of F. proliferatum were significant predictors of disease progression. The invasion of the pathogen led to a substantial decrease in nutrient elements in bamboo roots, except for nitrogen. Furthermore, the pathogen presence correlated with seasonal changes in the bamboo root microbiome and decreased bacterial richness in diseased plants. The root microbial community structure of healthy plants was more stable than that of their diseased counterparts. The potassium tissue content and the disease lesion area were identified as factors linked with the observed changes in the bamboo root microbiome. This study provides a theoretical foundation for understanding the seasonal dynamics F. proliferatum, an economically important soilborne pathogen of hybrid bamboo grown in Sichuan Province, China.